A New Direction of Learning Science of Kalam in State Islamic University - Damanik, Nurliana; Surya, Maulana Andi (Al-Hayat: Journal of Islamic Education, 2023)
This article aims to explain the development of learning kalam science, which has become one of the mandatory subjects for all study programs at State Islamic Religious Universities (PTKIN). To understand the new direction of kalam science learning, this research focuses on several formulations, such as the trajectory of kalam science learning, the orientation, and the inclusiveness of kalam science learning at PTKIN. This research uses qualitative research with a case study approach. Data sources consist of lecturers and students involved in learning natural sciences. Observation, interviews and documentation were carried out for data collection. Data analysis with stages of categorization, interpretation and presentation. The findings of this research explain that the learning trajectory of natural sciences at PTKIN has shifted from the IAIN era, which was ideological-subjective, to the UIN period, which was more ideological-objective. Meanwhile, the orientation of learning kalam sciences has also changed from being focused on preaching to scientific development. The new direction of learning natural sciences at PTKIN has demonstrated inclusive learning, characterized by accepting differences and finding common ground and reason among students. This research confirms that the inclusive attitude of learning kalam science has positively impacted creating a harmonious society amidst disagreements.